Graph theory-based radial load flow analysis to solve the dynamic network reconfiguration problem - Aman, M.M.; Jasmon, G.B.; Bakar, Ab Halim Abu; Mokhlis, Hazlie; Naidu, K. (Wiley, 2016)
Radial load flow (RLF) methods are frequently used in solving distribution system problems. The conventional Jacobian-based load flow methods (e.g., Newton-Raphson) may fail to converge in solving distribution system due to high resistance to reactance ratio of distribution lines. RLF methods are based on sweep-based mechanism and require that the line data must be arranged in accordance with network topology. This problem needs special attention particularly in case of solving dynamic power system problems, where topology of the network changes with tie switches position (network reconfiguration problem). This paper has presented an intelligent graph theory-based RLF analysis to solve "dynamic" problems. The proposed algorithm will help in arranging line data for any combination of tie switch positions, to check the radiality of the system and to ensure that all nodes are connected with the source node. The effectiveness of the proposed method is also validated by solving 16-bus and 33-bus network reconfiguration problem using graph theory-based RLF method.